Synthetic Analysis on Radar Cross-Section and Remote Sensing for an Ornithopter - Zhou, Zeyang; Huang, Jun (Bio-Robotics, 2025)
To learn remote sensing features and radar cross-section (RCS) of a biorobotics ornithopter, a conjoint analysis approach built on remote sensing imaging and dynamic electromagnetic scattering is presented. The fuselage model of this flapping-wing aircraft adopts a low-scattering configuration design, with a pair of wings located on both sides of the front fuselage. High-fidelity unstructured mesh technology is utilized to model the surfaces of wings and fuselage. Linear transformation is employed in analyzing remote sensing grayscale, and dynamic electromagnetic scattering methods are applied to obtain the RCS of objects. The results show that this method can acquire the remote sensing grayscale characteristics of the ground and the ornithopter; however, the presence of some ground objects makes it difficult for flapping-wing machines to be identified. Compared to the forward case, there are more azimuths in the lateral direction, which are beneficial in reducing the average and peak indicators of the dynamic RCS of the ornithopter. Considering the case of tail incidence, the peak and mean RCS of the ornithopter show a tendency to first decrease and then grow within a given range. Low-grayscale water bodies and boundary areas with significant grayscale differences are advantageous for quickly identifying the ornithopter.